VARIASI VOLUME DAN WAKTU PEWARNAAN WRIGHT-GIEMSA TERHADAP KUALITAS MORFOLOGI SEL POLIMORFONUKLEAR - Zaky Wahyudin; Nur Aini Hidayah Khasanah (Ensiklopedia Research and Community Service Review, 2026)
Abstract : Peripheral Blood Smear (PBS) examination is a crucial method for evaluating blood cell morphology, including polymorphonuclear (PMN) leukocytes, whose appearance is highly dependent on staining quality. Wright–Giemsa staining is widely used because it provides excellent contrast between the nucleus, cytoplasm, and cytoplasmic granules. This study aimed to determine the effect of staining volume and staining time on the morphological quality of PMN cells. A true experimental study with a post-test-only design was conducted using six EDTA-anticoagulated blood samples that met the inclusion criteria. Three staining volumes (1.5 mL, 2.0 mL, and 2.5 mL) and three staining times (8, 12, and 16 minutes) were evaluated. The Kruskal-Wallis test demonstrated that variations in staining volume and staining time significantly affected PMN morphological quality (p 0.05). Post hoc Mann–Whitney analysis showed that the optimal staining combinations for basophils and eosinophils were 8 minutes–2.0 mL, 12 minutes–1.5 mL, 12 minutes–2.5 mL, 16 minutes–1.5 mL, and 16 minutes–2.0 mL, producing optimal contrast of nuclear, cytoplasmic, and granule staining. For neutrophils, the optimal combinations were 8 minutes–2.0 mL, 12 minutes–1.5 mL, and 16 minutes–1.5 mL. The 8-minute–2.0 mL combination is recommended as the optimal staining condition because it provides high-quality staining while minimizing staining time and reagent consumption. In contrast, the 16-minute–2.5 mL combination resulted in over-staining, making PMN morphology difficult to evaluate. Further studies should investigate staining times shorter than 8 minutes and a wider range of staining volumes to determine the minimum conditions required for optimal staining quality.Keywords: peripheral blood smear, polymorphonuclear cell morphology, staining volume, staining time, Wright-Giemsa.